High-pressure optical floating-zone growth of Li(Mn,Fe)PO4 single crystals - Neef, Christoph; Wadepohl, Hubert; Meyer, Hans-Peter; Klingeler, Rüdiger (Journal of crystal growth, 2017)
Mm-sized LiMn1−xFexPO4 single crystals with 0⩽x⩽1 were grown by means of the traveling floating-zone technique at elevated Argon pressure of 30bar. For the various doping levels, the growth process was optimized with respect to the composition-dependant effective light absorption and transparency of the materials. A convex crystal/melt interface, determined by the angle of incident light, was identified to be particularly crucial for a successful growth. The resulting large single crystalline grains are stoichiometric. Structure refinement shows that lattice parameters as well as the atomic positions and bond lengths linearly depend on the Mn:Fe-ratio. Oriented cuboidal samples with several mm3 of volume were used for magnetic studies which imply an antiferromagnetic ground state for all compositions. The Néel-temperature changes from TN=32.5(5)K in LiMnPO4 to 49.5(5)K in LiFePO4 while the easy magnetic axis in the ordered phase flips from the crystallographic a- to the b-axis upon Fe-doping of x<0.2.